Leave no one behind: Prioritising equality and equity towards integration of global sustainability governance - Lisa Hiwasaki (Earth System Governance)
Processes within global sustainability governance are fragmented despite calls for greater synergies. Although “leave no one behind” is a universal value of the 2030 Agenda for Sustainable Development, evidence of concrete efforts to decrease inequalities, especially between countries in the Global South and North, are limited. In order to understand the impacts of fragmented global sustainability governance on inequality reduction and equitable development, I conducted text analysis of the 2030 Agenda's Sustainable Development Goals, the Paris Agreement on climate change, and the Sendai Framework for Disaster Risk Reduction, and reviewed literature on the convergences and gaps among them. I found that first, although the three global agreements acknowledge the need to realise equality and equity, the use of these terms are sparing in the texts, and when they do appear, they are defined inconsistently and operationalized imprecisely across these global processes. Second, while numerous linkages exist among the three agreements, sustainability challenges that directly relate to equality and equity outcomes are the ones with the least convergences identified, and have the least number of activities implemented, research done, and data collected. Such fragmented and inconsistent implementation and monitoring of progress towards sustainable development are detrimental to equitable development, and negatively affect marginalised groups—especially in the Global South—for whom impacts of disasters, climate change, and maldevelopment are felt most acutely. At more than halfway in the implementation of these global processes, it is important now more than ever to strengthen efforts towards their integration by prioritising equality and equity.